"Wieder in dieses normale zivile Leben reinkommen": zur Bedeutung von Normalität im Wiedereingliederungsprozess haftentlassener Sexualstraftäter : Teilstudie 1 der Langzeitstudie "Sexualstraftäter in den sozialtherapeutischen Abteilungen des Freistaates Sachsen" - Gauder, Kira-Sophie (Schriftenreihe des Max-Planck-Instituts für ausländisches und internationales Strafrecht, 2021)
In recent years, the study of desistance has become a major criminological research topic. However, despite the fact that sex offenders receive significant media and societal attention, the actual life course of released sex offenders is rarely examined. We know little about their reentry processes and subjective experiences during their transition from prison. This doctoral thesis presents the results of an empirical research project that analyzed the post-release life courses of sex offenders in order to gain insights into their subjective experiences during the reentry process as well as the dynamics and interrelationships involved. The overall research questions covered are: 1) What does the life course of sex offenders look like after release from prison? 2) What shapes the life course of this group of offenders? 3) How do released sex offenders experience their reentry? The dissertation forms part of the larger longitudinal research project “Sexual Offenders in the Social Therapeutic Institutions of the Free State of Saxony” conducted by the Max Planck Institute for Foreign and International Law (since 2020: Max Planck Institute for the Study of Crime, Security and Law) in Freiburg i.Br. While a wide range of empirical data were collected during the longitudinal project, the doctoral dissertation project focused on the analysis of sixty-nine semi-structured interviews with released sex offenders. The study is explorative in nature and has an inductive approach. This provides insights into the social reality and lives of released sex offenders. The analysis was carried out in two steps, beginning with an in-depth analysis of a sub-sample (n = 12). Subsequently, the whole sample (n = 69) was analyzed in a more systematic manner using an inductive coding guide. This approach assists in better understanding the multifaceted reentry process. On the one hand, different aspects of the post-release life course are identified, including experienced difficulties described by the interviewees, their social environment, and their appraisal of correctional release preparation as well as post-release resocialization measures. These aspects significantly shaped the post-prison lives of the interviewees. Furthermore, more complex dynamics are uncovered, such as the framing of desistance and the internalization of stigmatization. On the other hand, different efforts on the released offenders’ side to reestablish a so-called “normal” life are traced. It proved to be the core dynamic in the reentry process and, consequently, the major findings of the present analysis concern the released offenders’ struggle to (re)establish normality. This volume presents various strategies that the interviewees used to (re)establish normality and illustrates how they are linked to other facets and phenomena in the post-release life course.